"Adhering to the Community" (Luzūm al-Jamāʿa): Continuities between late Umayyad Political Discourse and "Proto-Sunni" Identity1. Issue 2 (August 2015) - Barzegar, Abbas
Abstract: This article addresses the early formation of Sunni "orthodoxy" through the prisms of historical memory and collective identity rather than those of theology, law, and formal political power. 2 It does so by exploring the socio-political context in which the phrase luzūm al-jamāʿa 3 (adhering to the community) was deployed during the late Umayyad/Marwanid (64/684–132/750) and early Abbasid (132/750–333/945) periods, primarily among the networks of hadith transmitters who circulated the idea during that period. The results of this analysis reveal that ideas central to Sunni conceptions of community first developed in Umayyad patronage structures and networks, before being adopted by the so-called "proto-Sunni" elite.